2015
DOI: 10.1177/1076029615623375
|View full text |Cite
|
Sign up to set email alerts
|

Patient Characteristics and Antithrombotic Prescribing Patterns in Patients With Atrial Fibrillation in Tasmania

Abstract: Limited data are available on atrial fibrillation (AF) and its clinical management and outcomes from an Australian perspective. This study was designed to examine the patient characteristics and antithrombotic treatment patterns among patients with AF in Tasmania, Australia. This retrospective observational study reviewed and followed patients with AF admitted to Tasmania's 3 major hospitals between January 2011 and June 2012. Patients were excluded if they had only 1 episode of AF that reverted spontaneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Physician preferences make a significant contribution to guideline non-adherence, particularly those related to their beliefs and practice patterns. [64,68,85] Prescribers usually focus on the risk of bleeding associated with OACs rather than the risk associated with not prescribing anticoagulants. [20,35,54,58,70,76,80,85] Reports from qualitative studies indicate that prescribers use formal stroke risk assessment tools but few use formal bleeding assessment tools.…”
Section: Physician-related Factorsmentioning
confidence: 99%
“…Physician preferences make a significant contribution to guideline non-adherence, particularly those related to their beliefs and practice patterns. [64,68,85] Prescribers usually focus on the risk of bleeding associated with OACs rather than the risk associated with not prescribing anticoagulants. [20,35,54,58,70,76,80,85] Reports from qualitative studies indicate that prescribers use formal stroke risk assessment tools but few use formal bleeding assessment tools.…”
Section: Physician-related Factorsmentioning
confidence: 99%
“…Interestingly, after the introduction of the DOACs, similar rates of anticoagulant prescribing to high-risk patients have been reported by Pandya et al [28] of 54% from a hospital in New South Wales. Three Tasmanian studies have also reported comparable rates with studies by Bista et al in the early post-DOAC era finding 52.5% [29] and 55.6% [30] of high-risk patients received anticoagulants, while Admassie et al [20] found this increased to 60.7% in a study ranging from 2010 to 2015. Further to this, in rural Western Australia Bellinge et al [31] found 69% of patients with AF received oral anticoagulant therapy during hospital admission, but this was for patients with a CHA₂DS₂VASc scores ≥ 1.…”
Section: Resultsmentioning
confidence: 53%
“…Several factors contribute to OAC undertreatment in AF. Most of the previous studies that reported factors associated with thromboprophylaxis undertreatment in AF were based on findings from retrospective studies and largely outside of the general practice setting 7,10,13–15 . Nonetheless, a previous review article identified that prescriber‐related factors, including their beliefs and practice patterns, were among the major contributors 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous studies that reported factors associated with thromboprophylaxis undertreatment in AF were based on findings from retrospective studies and largely outside of the general practice setting. 7,10,[13][14][15] Nonetheless, a previous review article identified that prescriber-related factors, including their beliefs and practice patterns, were among the major contributors. 8 Previous qualitative studies reported that more emphasis is given to bleeding than stroke prevention when prescribing OACs, although with limited use of formal bleeding risk assessment tools by prescribers.…”
Section: Introductionmentioning
confidence: 99%